Rekonstruksi Tanggung Jawab Spiritual Orang Tua Kristen terhadap Anak dalam Pendidikan Agama Kristen di Tengah Keluarga: Analisis Teologis-Pedagogis - Boby Andika Sinaga; Melda Br. Tarigan; Sripinta (PT. PENERBIT TIGA MUTIARA, 2026)
Christian Religious Education within the family is currently confronted with significant challenges arising from social change, the rapid advancement of digital technology, and the declining involvement of parents in nurturing their children's faith. These conditions highlight the need to reconstruct the spiritual responsibility of Christian parents so that the family may once again serve as the primary center of faith formation. This study aims to analyze the essence of Christian parents' spiritual responsibility from theological and pedagogical perspectives, explain its implementation in Christian Religious Education within the family, and examine its implications for the development of children's faith, character, and spirituality. This study employed a descriptive qualitative approach using a library research method. The findings reveal that parents' spiritual responsibility is manifested through exemplary living, faith-based communication, spiritual discipline, and sustainable family relationships. The study also proposes a conceptual model consisting of four main components: theological foundation, pedagogical relationship, family spiritual practices, and children's character transformation. It is concluded that reconstructing parents' spiritual responsibility strengthens the family as the primary context of Christian Religious Education while fostering synergy among families, churches, and educational institutions. The novelty of this study lies in integrating theological and pedagogical perspectives into a contextual, dialogical, participatory, and transformative model for reconstructing the spiritual responsibility of Christian parents.